Design and analysis of a mechanical ventilation system based on cams - Calderón, J.A.; Rincon, C.; Agreda, M.; de Cisneros, J.J.J. (Elsevier, 2021)
Low-cost mechanical ventilators have been developed in order to deal with the shortage of traditional ventilators whose quantity is not sufficient in an emergency context in Perú. Protofy, a company from Spain, designed one of the first low-cost mechanical ventilation systems OxyGEN which was approved by a medicine agency in its country in special context of COVID 19. Therefore, as main of this article, a redesign of this system named OxygenIP.PE was carried out according to local requirements and available technology, but maintaining its working concept based on compression mechanism by cams. Sensors were added and a control algorithm of the respiratory rate was developed. Ventilation curves monitoring over time was implemented; in this sense, a mathematical model of the whole system was developed. OxygenIP.PE was redesigned, fabricated, and tested measuring its ventilation curves over time. Results indicate that this redesign provides a sturdy equipment able to work during a longer lifetime than the original. The replicability of the ventilation curves behavior is ensured, while the mechanism dimensions are adapted for a particular airbag resuscitator. The mathematical model of the whole system can satisfactorily determine the ventilation curves over time and is used to show the air pressure, volume, and flow as a function of the compression arm's angular position and differential pressure through the breathing circuit measurement, furthermore the algorithms designed as a consequence of the mathematical model were implemented for Raspberry and ARDUINO microcontrollers. There were obtained parameters of pressure 10–65 cmH2O, airflow 50–65 l/m, volume 0–0.5 l, at two values of beat per minute (BPM) 15 and 25.
Keywords: Mechanical ventilation design; Low-cost mechanical ventilator; Experimental ventilation curves; Mechanical ventilation mathematical model; COVID-19; https://purl.org/pe-repo/ocde/ford#3.02.08